2018
DOI: 10.26508/lsa.201800139
|View full text |Cite
|
Sign up to set email alerts
|

Secretory granule protein chromogranin B (CHGB) forms an anion channel in membranes

Abstract: The CHGB subfamily of secretory granule proteins forms a new family of anion-selective channels by interacting with membranes via two amphipathic α-helices. The channel exhibits higher anion selectivity, larger conductance, higher DIDS-binding affinity, and higher Cl− sensitivity than other known anion channels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Future study will be needed to identify the iTAFs as we did previously (see Ref. 65) and to verify their functions in both telomerase-positive and -negative cells.…”
Section: Itafs Differ From Other Proteinaceous Factors That Regulate mentioning
confidence: 88%
“…Future study will be needed to identify the iTAFs as we did previously (see Ref. 65) and to verify their functions in both telomerase-positive and -negative cells.…”
Section: Itafs Differ From Other Proteinaceous Factors That Regulate mentioning
confidence: 88%
“…An increase in calcium in vascular smooth muscle cells leads to an augmented muscular tone which further increases vascular resistance that eventually raises the blood pressure [38]. One such gene is CHGB [39] that stimulates catecholamine secretion [40]. Common genetic variation at the CHGB locus, especially in the proximal promoter, influences CHGB expression, catecholamine secretion and the early heritable responses to environmental stress and is associated with changes in blood pressure in the sub-Saharan African and European ancestry groups [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, carboxypeptidase E, a prohormone sorting receptor, also interacts with lipid rafts via an amphipathic α helix . Recently, CgB has been shown to be able to penetrate inside biological membranes through its helicoidal domains to form an anion channel . Concerning CgA, several studies showed that the deletion of its N‐ or C‐terminal domains altered its secretion in distinct neuroendocrine cell lines .…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hormentioning
confidence: 99%
“…54 Recently, CgB has been shown to be able to penetrate inside biological membranes through its helicoidal domains to form an anion channel. 55 Concerning CgA, several studies showed that the deletion of its N-or Cterminal domains altered its secretion in distinct neuroendocrine cell lines. 10,35,50,56 Interestingly, the sequence identity between vertebrate CgA proteins is restricted to these terminal regions, 57 and expression of frog CgA in non-endocrine COS7 cells also resulted in the biogenesis of CgA-containing granules which release CgA and coexpressed hormones upon stimulation.…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hmentioning
confidence: 99%
See 1 more Smart Citation